Płyty Plastycznie Niejednorodne i Ortotropowe w Stadium Zniszczenia - Niepostyn, D. (Engineering Transactions, 1962)
The limit load of a plate can be determined by considering the dissipation power of internal and external forces connected with the field of displacement rates, Making use of the theory of plastic strains work or displacement can be used. The research of the correct form of the deflection surface reduces to the minimum problem of the total work of the internal and external forces. On the basis of an analysis for non-homogeneous and orthotropic plates in the plastic state it is shown that the deformed surface should be rectilinear. The yield condition used for this purpose is represented by a rectangle in the system of principal moments. Rigid-plastic properties are assumed. Solutions are given for a plate on hinged support and clamped along the contour. The correct: form of the negative crack lines is sought by means of the variational calculus. The family of curves (5.2.5) constitutes the solution of the problem. The works of the internal forces along a negative crack and in an internal region are expressed by similar integrals differing merely by the value of the collapse moment. The results are applied to a polygonal plate loaded by 4 concentrated force and a rectangular plate loaded by a uniformly distributed force.